2009
DOI: 10.1021/bm801361f
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Fucoidan and Chitosan Sulfate on Chitosan Modified PET Films Monitored by QCM-D

Abstract: The adsorption behavior of fucoidan as well as chitosan derivatives (chitosan sulfate) on poly(ethylene terephthalate) (PET) model film surface was studied using the quartz crystal microbalance technique. These systems were chosen for this study due to their promising biocompatible properties. Moreover, fucoidan and chitosan sulfate have promising anticoagulant properties and represent an alternative to heparin treatment of vascular grafts. As a first step, PET foils were activated by alkaline hydrolysis to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 26 publications
1
30
0
Order By: Relevance
“…It has been reported that chitosan (Ch) can improve the binding of sulfated polysaccharides. [14] However, chitosan is isolated from different natural sources (e.g., crab or squid shells) and may differ in its degree of N-acetylation, MW, and the amount of protein residues. [18] Thus, 6-deoxy-6-aminocelluloses were tested as anchor layers in the present study as well.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been reported that chitosan (Ch) can improve the binding of sulfated polysaccharides. [14] However, chitosan is isolated from different natural sources (e.g., crab or squid shells) and may differ in its degree of N-acetylation, MW, and the amount of protein residues. [18] Thus, 6-deoxy-6-aminocelluloses were tested as anchor layers in the present study as well.…”
Section: Resultsmentioning
confidence: 99%
“…Although the present study involved only a single adsorption step and fucoidan containing films have been prepared by multiple adsorption of the polysaccharide on chitosan-coated PET films, the final shift factors were in a similar range (fucoidan: DF % -17 Hz, CS: DF % -19-29 Hz). [14] In the later case, most of the additionally attached fucoidan multilayers have been removed by the final rinsing step while only a small frequency increase by polysaccharide desorption was observed for rinsing of CScoated films. This finding leads to the assumption that CS and fucoidan are adsorbed to PS-NH 2 -coated PET films in a comparable way.…”
Section: Adsorption Of Cs On Pet Filmsmentioning
confidence: 97%
See 3 more Smart Citations